Criminal Application Exceeds the Maximum Limit of the Law in Child Criminal Cases - Dhea Wardah Aulia; Waluyadi Waluyadi (Ridwan Institute, 2026)
The imposition of criminal sanctions against children in conflict with the law in Indonesia is fundamentally regulated by Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, which limits maximum imprisonment to half of the adult penalty and restricts capital punishment. However, recent judicial practice reveals a significant legal discrepancy, as demonstrated by Decision Number 50/Pid.Sus-Anak/2024/PN.Plg where the prosecutor demanded the death penalty, and Decision Number 3/Pid.Sus-Anak/2024/PN.Pnj where the judge imposed a 20-year prison sentence, both exceeding the statutory maximum limits for child offenders. This research aims to analyze the basis of considerations from the public prosecutor and the panel of judges in applying penalties beyond the maximum limit of the law against children and to review their suitability with progressive legal approaches and substantive justice frameworks for society. The approach method used in the study was normative juridical, with a qualitative approach through literature studies of laws and regulations, court decisions, and other legal materials. The results of the study show that the basis for consideration from the public prosecutor and the panel of judges in applying the crime beyond the maximum limit of the law is based on the severity of the crime committed by the child, the social impact and the increase in criminal acts committed by the child, so that in the practice of sentencing it considers progressive law enforcement and the framework of substantive justice